Digital Exhaustion in relation to Video Games – The Consumer Perspective - Arkia, Noora (fi=Turun yliopisto|en=University of Turku|, 2015)
This thesis regards exhaustion of copyright’s distribution right in intangible transfers of video games. It analyses whether, under the current law of the European Union, the phenomenon of digital exhaustion, especially in relation to games exists. The thesis analyses the consumers’ position in the market for copyright protected goods. It uses video games market as an example of the wider phenomenon of the effect of latest technological developments on consumers. The research conducted for the thesis is mostly legal dogmatic, although also comparative analysis, law and economics and law and technology methods are utilised. The thesis evaluates the effects of the most recent case law of the European Court of Justice to analyse the current state of digital exhaustion. In the analysis of effects that the existence of digital exhaustion has, the thesis uses the consumers’ point of view. The thesis introduces the current state of technology in the field of video games from a legal perspective. Furthermore the thesis analyses the effects on consumers of a scenario that no digital exhaustion exists in the future. Such scenario under the recent European case law at the moment seems realistic. The conclusion of my research is most importantly that the consumer position in the market for digital goods has deteriorated and that the probable exclusion of the exhaustion for digital goods is another piece of evidence of this development. Most importantly however, the state of affairs where no certainty prevails on whether digital exhaustion exists, creates injustice from the consumers’ point of view. Accordingly, acts by EU legislators of the Court of Justice of the European Union are required to clarify the issue.